ANALYSIS ON TRAFFIC CONGESTION IN BANDARLAMPUNG: A SYSTEM DYNAMICS APPROACH - ABETO , MUHAMMAD
Traffic congestions have been usual scenery in many big cities in Indonesia currently and have became very complex and complicated problems of development, and are not easy to solve both in local as well at national levels. During the course of the time, such problem also became a common phenomena among lesser cities in Indonesia. Among those cities is Bandarlampung City which the capital of Lampung Province. That phenomena is reflected in the degree of road traffic saturation level (which is an indicator of congestion) which showing increasing level. Those increasing trends indicate that Bandarlampung has a very high possibility to experience congestions in the next few years when there is not any proper measures to overcome and control them. Recently the Bandarlampung Municipality has released a plan to construct flyovers to anticipate possibilities of traffic congestions in next few years. With the above backgrounds, this theses is trying to analyze and to discuss the traffic behaviors in Bandarlampung by using system dynamics methodological approach. The thesis is trying to describe and understand the traffic congestion from systemic point of view. Transportation is a system which contains several smaller systems with causal relations and interrelationships. At least there are three systems which constitute the transportation system, i.e.: activity system (e.g.: population and economic activities), infrastructures and transportation means (e.g.: roads and vehicles), and movement systems (e.g.: traffic volume and travel time). This thesis focuses on the problem of degree of saturation in Bandarlampung city's roads whose trends is increasing from year to year. Modeling with system dynamic approach is used to predict the degree of saturation behavior in the future as well to establish and to test several scenario on policy intervention, both those which have been planned or have not yet by the Bandarlampung Municipality Government, in effort to control the extent of roads' degree of saturation at a safe level from traffic congestion. There are several scenarios which have been tested and compared with the referential pattern (scenario without any policy interventions). It can be concluded that: (1) The degree of saturation in Bandarlampung is showing an increasing trend during the course of the years because of following factors: (a) higher growth of vehicle numbers in Bandarlampung, especially during the last 6 years in numbers of motorcycles and small size public transports, which is not anticipated by any growths in existing road capacity during the last 6 years; (b) higher influence of road side interferences (decrement factor of road capacities resulted from by activity of roadside like pedestrian, stop of other city transport and carriage, carriage of slow admission and roadside exit and carriage) as resulted by less discipline in the transportations management and enforcement of existing regulations. Road side interferences is increasing along with the increasing numbers of small size public transport in Bandarlampung. (2) Traffic congestion phenomena as currently experienced by other big cities in Indonesia, based on model simulation, is predicted will take place in Bandarlampung in several years to come, as showed by increasing saturation on existing roads, whenever there is no measures to anticipate and to overcome the congestion problems thoroughly in the long run. (3) Early adoption of alternative policies such as decision to develop establish a mass transport system, limitation of vehicle operational age, and special lane for motorcycle drivers, which aimed to slow down the increasing growth rate of vehicles (especially those privately owned ones) in Bandarlampung, based on model simulations, are policy alternatives which can be adopted to control and overcome traffic congestion in the long run. This is shown by desirable degree of saturation from simulations which can be sustained at a safe level from traffic congestion.